Dying on the vine - Elkins, Aaron J. (Elkins, Aaron J. Gideon Oliver novels., 2012)
In Tuscany visiting friends with his wife, Gideon Oliver is asked to reexamine the bones of a couple whose deaths were ruled a murder-suicide. His findings do not agree with those of the Italian police.